Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To find out how much more money is in Joel's account compared to Kevin's account [tex]\(x\)[/tex] weeks after the start of the year, we need to calculate the difference between the two functions [tex]\( j(x) \)[/tex] and [tex]\( k(x) \)[/tex].
Given:
[tex]\[ j(x) = 25 + 3x \][/tex]
[tex]\[ k(x) = 15 + 2x \][/tex]
We need to find the function [tex]\((j-k)(x)\)[/tex], which represents the difference between [tex]\(j(x)\)[/tex] and [tex]\(k(x)\)[/tex].
[tex]\[ (j - k)(x) = j(x) - k(x) \][/tex]
[tex]\[ = (25 + 3x) - (15 + 2x) \][/tex]
Now, we will simplify the expression step-by-step:
1. Distribute the negative sign through the [tex]\(k(x)\)[/tex] term:
[tex]\[ = 25 + 3x - 15 - 2x \][/tex]
2. Combine like terms:
[tex]\[ = (25 - 15) + (3x - 2x) \][/tex]
[tex]\[ = 10 + x \][/tex]
So, the function that correctly represents how much more money is in Joel's account than in Kevin's account [tex]\(x\)[/tex] weeks after the start of the year is:
[tex]\[ (j - k)(x) = 10 + x \][/tex]
Therefore, the correct answer is:
B. [tex]\((j - k)(x) = 10 + x\)[/tex]
Given:
[tex]\[ j(x) = 25 + 3x \][/tex]
[tex]\[ k(x) = 15 + 2x \][/tex]
We need to find the function [tex]\((j-k)(x)\)[/tex], which represents the difference between [tex]\(j(x)\)[/tex] and [tex]\(k(x)\)[/tex].
[tex]\[ (j - k)(x) = j(x) - k(x) \][/tex]
[tex]\[ = (25 + 3x) - (15 + 2x) \][/tex]
Now, we will simplify the expression step-by-step:
1. Distribute the negative sign through the [tex]\(k(x)\)[/tex] term:
[tex]\[ = 25 + 3x - 15 - 2x \][/tex]
2. Combine like terms:
[tex]\[ = (25 - 15) + (3x - 2x) \][/tex]
[tex]\[ = 10 + x \][/tex]
So, the function that correctly represents how much more money is in Joel's account than in Kevin's account [tex]\(x\)[/tex] weeks after the start of the year is:
[tex]\[ (j - k)(x) = 10 + x \][/tex]
Therefore, the correct answer is:
B. [tex]\((j - k)(x) = 10 + x\)[/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.